Sistem Pendeteksi Nominal Uang Kertas Bagi Tunanetra - Zhafirah Majdiyah Mustarum; Mardawia Mabe Parenreng; Nurul Khaerani Hamzidah; Mustarum Musaruddin (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2023)
This study introduces a banknote nominal detection tool designed to enable visually impaired individuals to determine the value of both Rupiah and Dollar banknotes. The system utilizes a TCS3200 sensor, integrated with an Arduino microcontroller, to read RGB data values when a banknote is placed on the sensor. The system then automatically compares the detected RGB values with predefined ranges, triggering an audio output on headphones or speakers that signifies the recognized banknote value. The primary objective of this tool is to enhance the independence of the visually impaired by providing a reliable means of identifying banknote denominations. By implementing this innovative solution, the risk of financial fraud against the visually impaired is mitigated, contributing to a more inclusive and secure economic environment. The experimental results demonstrate the efficacy of the designed system in detecting various Rupiah banknote denominations, including Rp 1,000, Rp 2,000, Rp 5,000, Rp 10,000, Rp 20,000, Rp 50,000, Rp 100,000, as well as US Dollar banknotes $1 and $5 from the 2022 emission.